The relationship between emotional intelligence on cognitive ability and job performance among agricultural extension agent in Malaysia agro-based industry - Fatin Syafiqah Najwa, Khairul Suhaimi (2024)
Agricultural extension agents play a crucial role in providing effective and efficient extension services by acting as a liaison between government agencies and farmers. However, the application of Emotional intelligence (EI) (Self-awareness, Self-motivation, Self-regulation and Relationship Management) to measure job performance in agricultural extension agent is still relatively new and continue to debate whether EI has a substantial relationship on emotion, cognitive along with societal practices. Therefore, this study focused on Malaysia’s Agro-based industries. First objective of the study is to investigate the effect of EI elements towards agriculture extension agents’ job performance. Secondly, to examine the EI element towards agriculture extension agents’ cognitive ability. Third, to examine the effect of cognitive ability on job performance among agriculture extension agents. The forth objective of the study is to investigate mediating role of cognitive ability on the relationship between EI element and job performance of agriculture extension agents. The study employed a descriptive quantitative analysis and CB-SEM analytic research utilising The Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT) and Wong Law Emotional Intelligence Scale (WLEIS). A total of 448 respondents from four Agro-based agencies in Malaysia were involved and resulted a significant correlation between elements of EI (self-regulation and relationship management) while other elements studied (self-awareness and self-motivation) did not found significance relationship between and the agricultural extension agents’ job performance. Throughout this study, it revealed EI elements (self-awareness, self-motivation and self-regulation) except for relationship management have a direct relationship towards cognitive ability among agriculture extension agents. In addition, there is also a strong relationship between cognitive ability and job performance among agriculture extension agents. For the mediation test, cognitive ability was positively mediate the relationship between EI elements and agricultural extension agents’ job performance except for relationship management. The findings theoretically support the application of EI approaches in task execution and information delivery, based on the Goleman Model. Practically, it is essential to use emotions precisely and according to different conditions to achieve the aims and objectives of public organizations. Therefore, EI should be aggressively used to raise awareness and maturity in the workplace for better performance.